(untitled) (Journal of the College of Basic Education, 2022)
The research deals with the truth and the metaphor of Allamah al-Hilli according to a contemporary linguistic vision and the rooting of this subject with Allama al-Hilli. The most prominent scholars of the Imamiyyah, and he has a great deal of ideas on which he built his writings and dealt with his subjects, and since the topic of truth and metaphor is one of the most important linguistic topics that affect the analysis of texts, especially the Qur’anic text, Allama al-Hilli stopped at this topic for a long time, through which he explained how to deal with the words used in terms of their truth or Its displacement of the metaphor, indicating the type of this truth, whether it is linguistic, customary, or legal.